2010
DOI: 10.1089/ham.2009.1049
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of High Altitude Illnesses among Unacclimatized Persons Who Acutely Ascended to Tibet

Abstract: Incidence of high altitude illnesses among unacclimatized persons who acutely ascended to Tibet. High Alt. Med. Biol. 11:39-42, 2010.-High altitude illnesses pose health threats to unwary travelers after their acute ascent to high altitude locations. The incidence of high altitude illnesses among unacclimatized persons who acutely ascend to Tibet has not been previously reported. In the present study, we surveyed the incidence of high altitude illness among 3628 unacclimatized persons who had no previous high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
35
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 7 publications
(11 reference statements)
6
35
3
Order By: Relevance
“…Using the AMS-CSS, the incidence of AMS in Chinese male soldiers at 3600 m was reported to be 57.2% (Ren et al, 2010), a value higher than that found in the present study (29.79%). Ren et al (2010) subjects traveled to Tibet (3600 m) by air, whereas our participants traveled by train and bus.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Using the AMS-CSS, the incidence of AMS in Chinese male soldiers at 3600 m was reported to be 57.2% (Ren et al, 2010), a value higher than that found in the present study (29.79%). Ren et al (2010) subjects traveled to Tibet (3600 m) by air, whereas our participants traveled by train and bus.…”
Section: Discussioncontrasting
confidence: 86%
“…Ren et al (2010) subjects traveled to Tibet (3600 m) by air, whereas our participants traveled by train and bus. In addition, our camp was located at ~3200 m rather than at 3600 m. It is well known that the incidence of AMS is influenced by the method of travel and the rate of ascent to high altitude (Schneider et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it caused one group of investigators to observe in respect of the EPAS1 gain of function mutations that "it raises the possibility that polymorphic variation in HIF2α [EPAS1] contributes to the marked differential susceptibility to erythrocytosis, reduced plasma volume and pulmonary hypertension in humans at high altitude" (39). Chronic mountain sickness occurs among Tibetans at a lower prevalence than Han lowlanders (1.2% compared with 5.6%) living in the Tibet Autonomous Region (4,46). Chronic mountain sickness remains at that low level throughout adulthood among Tibetans but, in Peruvians, prevalence increases with age from approximately 13% in 20 to 39 y olds to approximately 36% in 55 to 69 y olds at 4,300 m (47).…”
Section: Discussionmentioning
confidence: 99%